Germinación Y Crecimiento En Vivero Y En Campo De Zaya (Amoreuxia palmatifida DC.), Una Especie Nativa Amenazada En México - Hernán Celaya-Michel; Andrés Ochoa-Meza; Jesús López-Elías; Miguel Ángel Barrera-Silva (European Scientific Journal, ESJ, 2017)
The food needs by the human population is increasing; In that sense, having a new crop can contribute to ameliorate the demand for food. The zaya (Amoreuxia palmatifida DC.) has been used as food both before and after the arrival of the European settlers in several states of northwest Mexico and southwestern United States. Over a hundred years ago there are authors recommending the zaya as a native plant with potential to be cultivated, being one of the problems to overcome the difficulty of its seeds to germinate. The study objectives were to evaluate germination treatments of zaya seeds and measure plantula grow under two systems. It was found that seeds physically scarified by sanding were those that germinated (73%; p <0.0001), compared to treatments control, of soaking for 24 hours and addition, of boiling water, were does not germinate any seed. The results of zaya growth were greater (p <0.0001), for plants in open field under drip irrigation, compared to the plants planted in pots under shadehouse, for all variables evaluated. The results obtained in this work, about the germination and growing of zaya, can be used to multiply their propagules and restore natural populations affected in northwest of Mexico. It is necessary to continue research on agronomic aspects of the zaya cultivation, a plant with great potential for both human and animal feeding, ornamental, and possibly medicinal use.